The effects of acute exercise and virtual reality tasks on children`s memory function and exercise preference - Krommidas, C.; Galanis, E.; Tzormpatzakis, E.; Hasandra, M. M.; Hatzigeorgiadis, A.; Morres, I. D.; Comoutos, N.; Theodorakis, Y. (International Journal of Kinesiology & Sports Science, 2022)
Background: It is well established that regular participation in exercise and virtual reality (VR) environments are important tools for improving or maintaining human health and cognitive function. Objectives: This study examined the effects of acute exercise and VR environments on children`s memory function and exercise preference (i.e. cycling with or without the use of VR technology). Methods: ? 2×3 factorial design was adopted with two measures (pre, post) and three study groups. Forty-five healthy children aged 9 to 13 years (Mage = 10.91±1.24 years) voluntarily participated in the study. Participants were randomly assigned into three groups receiving different treatment: (1) an exercise+VR group that cycled for 15 min in a VR environment (forest path) combined with basic mathematical problem-solving tasks, (2) an exercise group that cycled for 15 min, and (3) a no-exercise group that sat in a specific place in a lab for 15 min (the control group). Before and after the acute exercise, all the groups completed the Sternberg Memory Task. Upon completion of the intervention, the two exercise groups completed measures of enjoyment, intention and attitudes towards cycling. The exercise+VR group also completed a scale capturing the VR`s usability. Results: The results show that the exercise group scored higher on Sternberg`s Memory Task (p <.05) after the acute exercise treatment (post) than before it (pre). Similarly, the exercise+VR participants scored higher on the post-intervention memory task than did the exercise and control groups (p <.05). Moreover, the exercise+VR group reported higher scores on enjoyment, intention and attitude towards cycling than the exercise group, but this difference was not statistically significant (p >.05). Finally, the exercise+VR participants recorded high scores on the usability of the VR system during the acute exercise programme. Conclusions: These findings are in line with those of previous studies, underlining the important roles of exercise and VR environments on youths` cognitive function.